SOIL TYPE CLASSIFICATION FOR IDENTIFICATION OF SUITABILITY OF RESIDENTIAL AREAS USING THE SMCA METHOD IN PURBALINGGA REGENCY - kurnia anggraini, kurnia (International Remote Sensing Applied Journal, 2024)
The assessment of land suitability for residential development is an important aspect of sustainable urban planning. This study uses spatial multi-criteria analysis (SMCA) as a tool to identify potential land suitable for the development of residential areas in Purbalingga Regency, by considering soil type as the main variable. The method used involves using a soil-type map of Purbalingga Regency in 2018 as basic data. The classification of soil types is carried out to determine the spatial distribution of soil-types in the region, which includes alluvial, andosol, gleisol, cambisol, Mediterranean, Oxisol, Regosol, Settlement, and Water Body soil types. This study focused on weighting soil types based on suitability for residential areas, where each soil type was scored based on its level of suitability: very inappropriate (score 1), not suitable (score 2), quite suitable (score 3), and very suitable (score 5). The results of the analysis showed that the type of cambisol soil dominates the area with an area of 33,499.934291 hectares. However, the suitability of settlements based on the type of land is generally included in the category of non-conforming. This indicates that although the type of cambisol soil has a large area, its characteristics are less supportive for the development of residential areas. This research can be the basis for determining the optimal location for the development of sustainable settlements in accordance with local land characteristics.